What Explains Germany's Rebounding Export Market Share? - Joutz, Frederick (IMF Working Papers; Working Paper ;, 2007)
Germany's export market share increased since 2000, while most industrial countries experienced declines. This study explores four explanations and evaluates their empirical contributions: (i) improved cost competitiveness, (ii) ties to fast growing trading partners, (iii) increased demand for capital goods, and (iv) regionalized production of goods (e.g. offshoring). An export model is estimated covering the period 1993-2005. The dominant factors explaining the increase in market share are trade relationships with fast growing countries and regionalized production in the export sector. Improved cost competitiveness had a comparatively smaller impact. There is no conclusive evidence of increased demand for capital goods.